Impact of the Village Fund Policy on Community Economic Empowerment during the Covid-19 Pandemic - Rita Martini; Zulkifli Zulkifli; Sulaiman Sulaiman; Kartika Rachma Sari; Sukmini Hartati; Tri Anggun Pratiwi (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: The goal of this study is to determine the effectiveness of village budget policies in community economic empowerment during the Covid-19 pandemic by analyzing the implementation of village funds.